APLIKASI INSTANT MESSAGING PADA JARINGAN LOKAL AREA BERBASIS CLIENT SERVER - Yulianeu, Aneu; Durahman, Nanang (LPPM STMIK DCI, 2015)
As the development of information technology is increasing rapidly influenced by the many discoverie s and scientific development so as to create a tool that supports the acceleration of technological development one of their communication systemsThe development of information and communication technologies are rapidly is encouraging companies to improve operational capabilities and services to customers. One of the information and telecommunications technology used by the company is an instant messenger technology.Instant Messenging technology is a new technology that can be used for communication between two or more people on a computer network, Tekonologi a new breakthrough in the development of information technology because of its excellence in providing ease of communication in real time.Â Keywords:Â Instant Messeger, Computer Networking, Teachnologi